Age- and race-dependence of the fibroglandular breast density analyzed on 3D MRI - Nie, Ke; Su, Min-Ying; Chau, Man-Kwun; Chan, Siwa; Nguyen, Hoanglong; Tseng, Tiffany; Huang, Yuhong; McLaren, Christine E.; Nalcioglu, Orhan; Chen, Jeon-Hor (Medical physics (Lancaster), 2010)
Purpose: The purpose of this study was to evaluate the age- and race-dependence of the breast fibroglandular tissue density based on three-dimensional breast MRI. Methods: The normal breasts of 321 consecutive patients including Caucasians, Asians, and Hispanics were studied. The subjects were separated into three age groups: Younger than 45, between 45 and 55, and older than 55. Computer algorithms based on body landmarks were used to segment the breast, and fuzzy c-means algorithm was used to segment the fibroglandular tissue. Linear regression analysis was applied to compare mean differences among different age groups and race/ethnicity groups. The obtained parameters were not normally distributed, and the transformed data, natural log (ln) for the fibroglandular tissue volume, and the square root for the percent density were used for statistical analysis. Results: On the average, the transformed fibroglandular tissue volume and percent density decreased significantly with age. Racial differences in mean transformed percent density were found among women older than 45, but not among women younger than 45. Mean percent density was higher in Asians compared to Caucasians and Hispanics; the difference remained significant after adjustment for age, but not significant after adjusted for both age and breast volume. There was no significant difference in the density between the Caucasians and the Hispanics. Conclusions: The results analyzed using the MRI-based method show age- and race-dependence, which is consistent with literature using mammography-based methods.